Comparing Surgical and Clinical Success Rates of Ahmed FP7, and Baerveldt 250 and Baerveldt 350 Glaucoma Drainage Devices. Issue 3 (12th March 2023) - Kilgore, Khin P.; Grosinger, Alexander J.; Liu, Liang Yen; Jamali, Sepideh; Arora, Nitika; White, Launia J.; Khanna, Cheryl L.
Abstract : Précis: Surgical and clinical success rates were similar among Ahmed FP7, and Baerveldt 250 and 350 glaucoma drainage devices at three years. Purpose: To compare rates of surgical and clinical success in patients with Ahmed FP7 (FP7), Baerveldt 250 (B250), or Baerveldt 350 (B350) glaucoma drainage devices (GDDs). Design: A retrospective cohort study. Methods: A total of 157 eyes of 129 adult patients with FP7, B250, B350 GDDs, and 190 eyes of 99 medically controlled glaucoma patients were enrolled at a tertiary care institution from August 2017 through July 2019. They were followed through April 2020. The main outcome measures included surgical and clinical failure. Surgical failure was defined as intraocular pressure (IOP) outside 5–21 mm Hg, IOP reduced <20% below baseline, additional glaucoma surgery, GDD removal, or no light perception. Eyes that did not meet their goal IOP ranges or required secondary glaucoma interventions were deemed clinical failures. Results: A total of 43 (12.4%) FP7, 36 (10.4%) B250, 78 (22.5%) B350, and 190 (54.8%) medically treated control eyes were enrolled. By the postoperative year 3 visit, 10 (23.2%) FP7, 11 (30.6%) B250, and 32 (41.0%) B350 eyes had met a surgical failure criterion ( P =0.127). There were no significant differences in the numbers of eyes meeting their IOP target ranges ( P =0.510), and rates of secondary glaucoma surgeries ( P =0.270). Overall clinical success was attained among 83.3% FP7, 81.8% B250, and 68.0% B350 eyes ( P =0.447). Conclusions: The GDD groups were similar in their rates of success, based on both the surgical and clinical success definitions.